Antidiabetic Power of Belalai gajah Plant (Clinacanthus nutans) - Albriyanti, Ariesta; Annisa, Nur; Putri, Ananda Dwi; Panjaitan, Ruqiah Ganda Putri (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the decrease in rat blood glucose levels, MDA levels, and the histopathological description of pancreas after giving ethanol extract of belalai gajah plant. This study used 25 rats, grouped into 5, namely normal control, negative control (CMC-Na 0.5% dose 2 mL/200 g b.w), positive control (glibenclamide dose 0.09 mg /200 g b.w), belalai gajah plant ethanol extract (dose 30 mg/200 g b.w., and 60 mg/200 g b.w). Prior to treatment, the rats were induced into diabetes with streptozotocin-nicotinamide. The content of belalai gajah plant was tested phytochemically and antidiabetic. Potential of belalai gajah plant was tested by induction for 14 days. The results showed that ethanol extract of belalai gajah plant contained alkaloids, flavonoids, steroids, terpenoids, and phenolics. The decrease in blood glucose and MDA levels in the group given the ethanol extract of belalai gajah plant at dose of 60 mg/200 g b.w. was the same as the dose of glibenclamide 0.09 mg/200 g b.w. The results of histopathological of pancreas showed that the ethanol extract of belalai gajah plant at dose of 60 mg/200 g b.w. could improve the structure of Langerhans islets in the pancreas of diabetic rats.